Correction to: Characteristics of therapeutic alliance in musculoskeletal physiotherapy and occupational therapy practice: a scoping review of the literature - Folarin Babatunde; Joy MacDermid; Norma MacIntyre (BMC, 2017)
Correction Following publication of the original article [1], an erratum was initiated in order to include supplementary material that was not updated and not included during the online submission of the authors' corrections. The additional corrections, included below, are to Appendix II. The original article has been corrected.